Preserving The History Through Interior Design : A Case Study The Tanjung Hotel Surabaya - Mohammad Ivansyah Ismail Kelvin Dumais; Astrid Kusumowidagdo; Stephanus Evert Indrawan (KREASI, 2016)
The development of the business hotel in Surabaya is growing rapidly, especially in the budget hotel segment. Besides the way of lifestyle influenced by technology to make people have a habit to share through social media. The uniqueness and the value contained in a hotel makes an appeal for people to make a recommendation which will indirectly boost the value of the hotel. Hence the need to create a hotel that is unique to the market segment that is able to reach many people is a good business opportunity for businesses in the hospitality industry. Increased competition and demand for the number of hotels tend to do a price war and create a business in the hospitality industry is becoming less healthy. However, it provides an opportunity for The Tanjung Hotel to rise and develop into a hotel that not only provide hotel facilities, but is able to provide customer experience .The Tanjung Hotel is a two star hotel which has a good value on the facility and the services. Located in the downtown of Suabaya on Panglima Sudirman numbers 43-45, street this hotel has 40 guest rooms, meeting room facilities, and ballroom to be rented. The Tanjung Hotel comes with the concept that Art Deco-style hotel nuances Dutch colonial heritage buildings in which it is raised by the value of history is contained in the hotel.